2022
DOI: 10.1088/1361-6595/ac4b64
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dynamics, instabilities and OH generation in a pulsed atmospheric pressure plasma with liquid cathode: a diagnostic study

Abstract: While plasma-liquid interactions have been an important focus in the plasma research community, the impact of the strong coupling between plasma and liquid on plasma properties and processes remains not fully understood. In this work, we report on the impact of the applied voltage, pulse width and liquid conductivity on the plasma morphology and the OH generation for a positive pulsed DC atmospheric pressure plasma jet with He-0.1% H2O mixture interacting with a liquid cathode. We adopted diagnostic techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 58 publications
(67 reference statements)
6
43
1
Order By: Relevance
“…Atmospheric pressure discharges formed with a liquid electrode are gaining intense attention in the last decades both for plasma fundamentals and promising applications such as synthetic ammonia and hydrogen (both are sustainable and clean energy) [1,2] , plasma biomedicine [3,4] , surface modification [5,6] , nanomaterial synthesis [7,8] , and so on. When the discharge is on, the liquid surface evaporates under the effects of interfacial exothermic reactions such as ion hydration, H and OH recombination, and plasma-induced heat transfer [9] . When water vapor transfers to the gaseous phase region, solvent and dissolved components may also diffuse to the discharge column along with the vapor [10] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Atmospheric pressure discharges formed with a liquid electrode are gaining intense attention in the last decades both for plasma fundamentals and promising applications such as synthetic ammonia and hydrogen (both are sustainable and clean energy) [1,2] , plasma biomedicine [3,4] , surface modification [5,6] , nanomaterial synthesis [7,8] , and so on. When the discharge is on, the liquid surface evaporates under the effects of interfacial exothermic reactions such as ion hydration, H and OH recombination, and plasma-induced heat transfer [9] . When water vapor transfers to the gaseous phase region, solvent and dissolved components may also diffuse to the discharge column along with the vapor [10] .…”
mentioning
confidence: 99%
“…A large impact of evaporation on the plasma kinetics is demonstrated, such as the production of the gaseous OH, H 2 O + , and NO x (if air is mixed or used as background gas) [15,17,18] . Important effects of coupled plasma-liquid surface deformation have been shown on the discharge breakdown and plasma instability, as well as enhanced in-volume mixing, convection, and energy dissipation into the aqueous phase [19][20][21] . Extremely limited penetration of electrons [22,23] and reactive neutral radicals in the plasma-liquid interface was proved by sensitive diagnostic and simulation works [24,25] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma jet used in this study is similar to the one reported in the previous literature . The plasma was generated at the tip of a tungsten needle electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma jet used in this study is similar to the one reported in the previous literature. 39 The plasma was generated at the tip of a tungsten needle electrode. A negative pulsed direct current (DC) voltage was applied to the tungsten needle by a DEI PVX-4110 high-voltage pulser.…”
Section: Methodsmentioning
confidence: 99%